Migration pattern and biochemical response characteristics of polylactic acid nanoparticles in pakchoi (Brassica chinensis L. cv. SuZhou) seedlings - Zhao, Xinye; Luo, Qing; Dai, Wenju; Deng, Yongyao; Yang, Ning; Zhu, Xu; Zheng, Yixuan; Li, Ying; Feng, Liangshan (Frontiers in Plant Science, 2026)
Nanoplastics represent an emerging class of pollutants that infiltrate aquatic and terrestrial environments through diverse pathways, posing significant threats to ecosystems. However, research on the accumulation and translocation mechanisms of biodegradable nanoplastics in plants remains limited. In this investigation, pakchoi (Brassica chinensis L. cv. SuZhou) was exposed to fluorescently labeled polylactic acid nanoplastics (PLA-NPs) in hydroponic solutions with varying concentrations (20 mg/L, 50 mg/L) and particle sizes (170 nm, 330 nm) to investigate the migration, distribution patterns, and associated toxicological responses of PLA-NPs in pakchoi. Both microscopic imaging and fluorescence semi-quantitative analysis confirmed that PLA-NPs of both tested particle sizes can enter the root system via the apical meristem and primary root-lateral root junction. Furthermore, PLA-NPs with a smaller particle size (170 nm) and higher concentration (50 mg/L) are more readily absorbed and accumulated by roots, and subsequently translocated to aboveground tissues. When roots were exposed to PLA-NPs, the activities of superoxide dismutase, peroxidase, and catalase in pakchoi significantly decreased, while hydrogen peroxide and malondialdehyde levels increased. Concurrently, soluble sugar, soluble protein, and chlorophyll content also changed. Moreover, the magnitude of these changes increased with the increase in PLA-NPs particle size and concentration. Collectively, PLA-NPs accumulate in pakchoi seedling roots, translocate to aboveground tissues, and potentially posing certain risks to human health through the food chain.